Prevalence of substance abuse among adolescents of urban and rural community in Surendranagar district, Gujarat - Jasani, Pratik K.; Jadeja, Yadeepsinh M.; Patel, Nitesh M.; Jadeja, Dhara Y.; Shrimali, Jayraj B.; Purani, Shyamal K. (International Journal Of Community Medicine And Public Health, 2019)
Background: According to the World Health Organization (WHO), substance abuse is “persistent or sporadic drug use inconsistent with or unrelated to acceptable medical practice.” Recently, substance abuse has been increasing among children and adolescents. Alcohol is one of the leading causes of death and disability globally and in India. Tobacco consumption is a major preventable cause of death, accounting for 13,000 deaths per day globally. This study was conducted to identify the prevalence of substance abuse and its pattern among adolescents in rural and urban community of Surendranagar district. Methods: It was a cross-sectional study carried out among 300 rural (150 from school and 150 from community) and 300 urban (150 from school and 150 from community) adolescents selected by simple random sampling. Data was collected and analysed by Statistical Package for Social Sciences and Microsoft excel have been used to generate graphs, tables, etc. Results: Prevalence of substance abuse in our study was 30.17%. Adolescents from rural community had higher prevalence (37.67%). Prevalence was significantly higher in males (55.33%) than compared to females (5%). Tobacco was most common substance abused by the adolescents. Conclusions: Prevalence of substance abuse was higher in rural compared to urban community and in males compared to females. Chewing form being the most common form of abusing the tobacco followed by smoking and drinking form in our study.